Effective designing and implementing a blended teaching approach in effective course delivery: a case study - Sen, Tushar (Infonomics Society, 2012)
The blended mode of learning has become increasingly popular in higher education. In this paper the effectiveness of various fusion/mixing competencies such as implementation of alternative group project based assessment, problem based teaching, integration with real world as 'active learning' competency and digital full course materials, online work load, discussion, presentation, feedback to student as 'active teaching & technological' competency and finally administrative I leadership competency such as grading visible for students, application of blackboard, students behavior etc. in effective course delivery, unit design and in effective course management on an undergraduate large core unit, "Process instrumentation and control-328" at Curtin University, Perth WA has been presented Students opinions (eVALUate results) reflects the use of a thoughtful designing of a blended teaching approach made by their instructor in the year of 2010 in terms of well-designed units rich with resources, workload, timely feedback, visible grading, good interaction, quality of teaching, assessment tasks, motivation and high satisfaction as very high 'positive learning experience' which exceeds the target of University and faculty agreement.